CLINICAL PROFILE OF DRUG-RESISTANT TUBERCULOSIS (DR-TB) PATIENTS DURING THE COVID-19 PANDEMIC AT RSUD DR. SOETOMO (JANUARY 2021 - DECEMBER 2021) (TITLE) - Valentina Alfianti Herdy Tamyn; Rebekah J. Setiabudi; Soedarsono; Ibrahim Syamsuri; Shofiuddin Al Mufid (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The emergence of the COVID-19 pandemic in 2019 has had an impact on all aspects of life, particularly global health. Indonesia is one of the affected countries. The Indonesian government has responded to the conditions of this pandemic, one of which is by imposing access restrictions to prevent the pandemic from spreading. This policy indirectly affects the community's activities, including the utilization of existing healthcare services. Meanwhile, available data show that one of the major issues that the Indonesian state is still dealing with is its status as the third country with the greatest number of TB (Tuberculosis) cases in the world, with some of the TB cases being classified as Drug-Resistant Tuberculosis (DR-TB).